Impact of comorbidity on physical function in patients with rheumatoid arthritis. Issue 3 (12th October 2009) - Radner, Helga; Smolen, Josef S; Aletaha, Daniel
Abstract : Background: Physical disability is a main outcome in rheumatoid arthritis (RA) which tends to increase with comorbidities. However, the extent to which comorbidities contribute to the multifactorial process of disability has not been investigated. Objective: To quantify the contribution of comorbidity to physical disability in patients with RA. Methods: In a prospective cohort study, age-adjusted Charlson comorbidity index (CCIA ), serial measurements of disease activity and functional disability (evaluated by the Health Assessment Questionnaire Disability Index, HAQ) of 380 patients with established RA seen at an outpatient clinic over 1 year (June 2007 to July 2008) were ascertained. The association between comorbidity and physical disability was assessed using analysis of variance (ANOVA) and adjusted general linear regression models. Results: Four patient groups with increasing levels of comorbidity (CCIA 0, 1–2, 3–4 and 5–9; potential range 0–38) were defined. Mean HAQ scores were significantly different across these groups (0.67, 0.80, 1.24, 1.40, respectively; p<0.001) and also when adjusted for disease activity, gender and disease duration in the regression model (0.84, 0.88, 1.14, 1.48, respectively; p<0.001). The effects of CCIA on disability were similar within different strata of disease activity: namely, remission (0.26, 0.31, 0.48 and 0.88, p<0.01); low disease activity (0.83, 0.78, 0.98 and 1.36, p<0.01); and moderate to high disease activity (1.22, 1.33, 1.70 and 1.91, p<0.01), and thus were independent of disease activity. Several sensitivity analyses, including the use of the Short Form Health Survey (SF-36), confirmed these observations. Conclusion: Physical disability becomes worse with increasing levels of comorbidity, irrespective of disease activity.